Considerations for educators in supporting student learning in the midst of COVID‐19 - Minkos, Marlena L.; Gelbar, Nicholas W. (Psychology in the schools, 2021)
COVID‐19 has presented a period of unprecedented challenge for schools in the United States. Thousands of school buildings across the country were closed in the spring of 2020 through the end of the school year to slow the spread of the global pandemic. Plans to reopen schools in many states remain uncertain as the virus continues to spread across communities. Current and future challenges are complex, with significant impacts on the global economy, health care system, and overall well‐being. When schools reopen, students will present with a wide variety of academic and social‐emotional needs, and schools will need to mindfully adjust systems and practices to meet the needs of their unique student population. This paper provides educators with suggestions on how to adapt existing multitiered systems of support using a trauma‐informed lens to support students during this unusual time.